ADSORBABILITY OF “TALPUS-RO” AND “TALPUS-KK” MOULD - Larisa E. Pustovaya; Tatyana A. Tyurina; Boris V. Talpa; Ekaterina M. Bayan (Advanced Engineering Research)
The adsorption activity of the “Talpus-RO” and “Talpus-KK” mould for methylene blue, and its sorptive capacity for various metal cations is investigated. The possibility of further utilization of waste materials is shown.